PENGARUH PEMBERIAN PUPUK ORGANIK CAIR BERBAHAN DASAR LIMBAH AIR CUCIAN BERAS DAN TEPUNG CANGKANG TELUR TERHADAP BEBERAPA SIFAT KIMIA VERTISOL DAN HASIL TANAMAN PAPRIKA (Capsicum annum var. grossum) - M. Koli; Diana Y. L. Serangmo; Lily. F Ishaq (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Vertisol is a type of soil that has high in clay content, and generally has low organic matter content and available Nitrogen (N). This condition could be improved by the application of liquid organic fertilizer (LOF). One of the LOF that can be used is LOF made from washing rice waste water and egg shells. A polybag trial was undertaken to evaluate the effect of the application of LOF on some chemical properties of Vertisol and paprika yields (Capsicum annum var. grossum).The research was conducted from July to October 2020. The research was laid out in a Randomized Block Design consisting of 5 treatments namely P0; without LOF, P1; 50 ml LOF, P2; 100 ml LOF, P3; 150 ml LOF, and P4; 200 ml LOF. There were three replicates for each treatment. Data observed were analyzed using Analysis of Variance (ANOVA) followed by 5% DMRT. The observed data included total- N, available P, available K, number of fruit, and fresh weight fruit. The results showed that the application of LOF based on on rice wastewater and egg shell flour could improved soil chemical properties of Vertisols and yield of capsicum. The best treatment was at the application of 200 ml that contributed a good total - N, available P and available K as well as the highest number of fruit and fresh fruit weight of capsicum.